Social Influence in Non-formal Community Financial Institutions (Arisan) - Samsiah Nelly; F. X. Suwarto; Niko Sudibjo; Rudy Pramono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study intends to explain the phenomenon of lifestyle in urban communities, lifestyle practices and social influences that often occur in arisan groups. On the topic of arisan, the writer will explain more in depth about the model of arisan practice, social influences and consumptive lifestyles in the arisan group. This study employs a descriptive exploratory approach and created by the use of a literature review or a literature study. The theory or concept method is implemented through the use of multiple sources, including books, scientific publications, and the internet. All descriptions of existing concepts are combined into a single framework of thought. From the research conducted, it was found that identity is an important thing in social gathering activities. Identity then arises because the existing social gathering activities are dominated by consumption patterns in it. From this consumption activity, a competition was born between its members to show who has a higher identity and who doesn't. The chairman of the arisan has great influence in influencing its members to follow all his orders under the pretext of the interests of arisan activities. This power is not realized by the members. The strong friendship between the chairman and the other members, makes them enter into a system where there is control and what is controlled.